Pengaruh Pendinginan Cepat Terhadap Kekerasan dan Struktur Mikro Proyektil Amunisi MU-5 TJ dengan Media Pendingin Berbeda - Gultom, Ricardo Fransisco; Hernawan, Sya’ban Tri (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2024)
Heat treatment is a change in the properties and microstructure of metals through controlled heating and cooling rates without changing the chemical composition of the metal. Heat treatment can increase the hardness of metals in everyday life and make them harder. The results of oven heating must be adjusted to the type of metal and the process. Helps prevent metal cracking and increases hardness. This study will discuss the effect of coolant on MU-5 TJ ammunition during heat treatment. All specimens were heat treated at a temperature of 300 ° C with a holding time of 5 minutes and immediately immersed in a cooling medium in the form of SAE 140 oil, coconut water, and propylene glycol liquid. The tests carried out were Rockwell hardness tests and microstructure tests. Based on the test results obtained, the hardness of each sample was different. The hardness value of the projectile without treatment was 77.27 HR, the hardness of the projectile with SAE 140 oil coolant was 79.73 HR, the hardness of the projectile with propylene glycol liquid coolant was 80.78 HR, with coconut water coolant The hardness of the projectile was 81.40 HR. The hardness test results on samples that were not heat treated were lower than those of ammunition that were heat treated. Among the heat treated specimens, the specimen with the highest hardness value was the sample that used coconut water as a cooling media.